Hubungan Dukungan Keluarga terhadap Tingkat Kekambuhan Klien dengan Resiko Perilaku Kekerasan - Alfiery Leda Kio; Gede Harsa Wardana; A.A. Gede Rai Arimbawa (Poltekkes Kemenkes Yogyakarta, 2020)
Clients with schizophrenia often experience relapse and should be treated again in hospital because the family cannot afford to overcome them. The family plays an important role in home client care, family support has a very important role in both emotional support, instrumental support, information support, and assessment support from the existing data, the patient's relapse rate with the risk of violent behavior in Bali Province Mental Hospital 2016 reached 70% and 60% of the recorded data who revisited for treatment. The purpose of this study was to determine the relationship between family support and clients’ relapse rate with risk of violence behavior. This study was a descriptive correlational research, the number of respondents was 40 respondents by using sampling namely incidental sampling with cross sectional approach. Data was analyzed by using spearman rank analysis. Based on Spearman Rank test results obtained p value was 0.000 < than determined significance level 0,05, this result showed that there was relationship between family support and clients’ relapse rate with risk of violence behavior in IPCU Ward of Bali Province Mental Hospital. The result of this study is expected to be an information to mental hospital as well as to the family in order to increase the support, role and family functions to reduce the relapse rate of clients who suffer from schizophrenia.